BIOAVAILABILITY OF POLLUTANTS IN WATER AND SOIL ENVIRONMENTS - Bilyk, Tetiana I.; Shtyka, Olga S.; Avdeyeva, Anastasia O.; Padalka, Anastasia O. (Proceedings of National Aviation University (archive), 2008)
The problem of xenobiotics bioavailability in soil and water medium is currently the object of considerable attention of scientists, environment activists, and policy makers. The concept of xenobiotics bioavailability is seldom defined precisely. Every branch of science explains it in its own way. In present publication we are trying to reveal the idea of bioavailability concept and to connect bioavailability definitions to the concept of water and soil system pollution.